Bioactivity and metabolic profiling of crude extracts from endophytic bacteria linked to Solanum mauritianum scope: Discovery of antibacterial and anticancer properties - Abraham Goodness Ogofure; Ezekiel Green (Heliyon, 2025)
Bacterial endophytes associated with Solanum mauritianum Scop. represent a promising source of novel bioactive compounds with potential antibacterial and anticancer properties. This study aimed to investigate the diversity, distribution, and bioactivity of crude extracts derived from endophytic bacteria, focusing on their effects against bacterial pathogens of public health relevance and two cancer cell lines. Fresh, healthy plant samples were collected, and endophytes were isolated using standard cultural techniques. Identification of the endophytes was carried out through conventional and molecular methods. The comprehensive profiling and characterization of crude secondary metabolites were conducted using Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometry (LC-QTOF-MS/MS) and Gas Chromatography-High Resolution Time-of-Flight Mass Spectrometry (GC-HRTOF-MS). The antibacterial activity and minimum inhibitory concentration were evaluated for the secondary metabolites using the Resazurin Microtitre assay. The anticancer activity of the metabolites was evaluated against A549 Lung carcinoma cells and U87MG Glioblastoma cells (ATCC culture cell lines). The result revealed a diversity of bacterial endophytes, including Pantoea species, Luteibacter sp. Bacillus safensis, Arthrobacter sp., and Bacillus licheniformis. These endophytes displayed distinct-tissue-specific distribution patterns within S. mauritianum. Metabolic profiling of three endophytes (P. ananatis, B. licheniformis, and Arthrobacter sp.) revealed 14 common and numerous unique metabolites. The crude secondary metabolites exhibited broad-spectrum antibacterial activity against reference strains of Bacillus cereus, Pseudomonas aeruginosa, and Staphylococcus epidermidis, where MICs as low as 0.125 mg/ml were recorded across several secondary metabolites of Pantoea ananatis, Bacillus licheniformis, and Arthrobacter sp. The cytotoxicity assays on UMG87 glioblastoma and A549 lung carcinoma cells revealed that the secondary metabolites did not induce cell death but instead promoted cell proliferation with different viability rates. While this proliferative effect limits their direct application as anticancer agents, it raises intriguing possibilities for their role in tissue regeneration or repair. This study provides critical insights into the microbial diversity of S. mauritianum and underscores the potential of its endophytic bacteria as sources of bioactive compounds with diverse biotechnological applications.